Инновационный подход к воспитанию этнотолерантной личности - Даумова, Б.Б. (My University, 2016)
The article author identifies pedagogical problems etnotolerantnogo and multicultural education of the younger generation, identifies the components of the model form etnotolerantnosti individual conditions for successful implementation of the dialogue of cultures in ethnically oriented education, is divided into recommendations for the formation of high school students of ethnic tolerance in a multicultural educational environment who have been successfully tested in the framework of the course etnotolerantnogo education, has proven to his own experience of methods of forming etnotolerantnoy competence of schoolchildren shows how by forming etnotolerantnoy competence can be solved the problem of inter-ethnic cooperation and cultural tolerance in multiethnic regions of Kazakhstan, puts forward the idea of creating a single educational and educational space, etnotolerantnoy educational environment.
Keywords: ethnotolerant competence; phenomenon of socialization; tolerance; ethnos